Material didáctico para desarrollar la competencia resuelve problemas de forma movimiento y localización en estudiantes de cinco años de la Institución Educativa N° 380 Santa Mercedes Putumayo 2024 - Alvarez Lopez, Rosa Esther (2025)
The purpose of the study was to evaluate the incidence of the didactic material for the development of the competence called “Solve problems of form, movement and location” in five-year-old schoolchildren of the I.E. N°380 Santa Mercedes, Putumayo, in the year 2024. The research presented a quantitative approach, under a structure that corresponds to a pre-experimental pretest-posttest design with a single group. The population of this study was formed by five-year-old schoolchildren and the sample was purposively selected and consisted of 15 children from the institution considered. The results of the study confirmed the improvement of the students' performance after the application of the didactic material. Consistently, the mean of the general competence goes from 13.76 in the pretest to 14.80 in the posttest with respect to the pretest mean (+1.04 points difference). On the other hand, the Student's t-test reported the value tc=-3.333 and p=0.000, which verifies that there is a statistically significant difference as a result of the improvement in the evaluated competence. It is concluded that the application of the didactic material evidenced a positive and significant effect in the development of the capacities linked to the evaluated competence, being remarkable the improvement in the capacity to execute strategies and procedures that favored the learning of geometry and spatial location.